EPIDEMIOLOGICAL PROFILE OF THE LIVE BIRTH IN A TOWN OF THE NORTH OF PARANÁ STATE, 2010 (Fiep Bulletin - online, 2012)
To find out the number of the live birth is necessary to enable health indicators in its economic, politician-social, and epidemiological aspects, and may represent the reality of a locality. This work aimed to learn the characteristics of the live birth in the year of 2010, in a town located in the North of Paraná State. It was a retrospective, descriptive, and quantitative research, developed by the variables contained in the declaration of live birth (DLBs). 438 (100%) DLB's were analyzed, verifying the following variables: gender, race, age of mother, prenatal diagnosis, number of medical appointments, previous gestations, index of apgar, type of birth, type of pregnancy, education level of the pregnant women, gestational age and weight of the newborn. With the study, it was able to observe that out of the 438 births, 55% were males, 87% white, the newborn predominant weight was from 2500 to 4000 kilograms in 86% of them. Regarding the type of birth, caesarean section represented 56% of the total. The predominant age was between 20 to 35 years (74%), however 19% were adolescents; the education level from 8 to 11 years of studies represented 51%. As it regards to prenatal diagnosis, 98% of the women had it and 65% went to 7 or more appointments; 54% of the pregnant women were multiparae. According to the results, it is able to say that the epidemiological profile of the live birth in the city of Bandeirantes is satisfactory, although some of the factors can be improved, such as the number of caesareans, the gestations in the adolescence, the premature birth and 100% of adhesion to prenatal diagnosis.
Keywords: Live birth; pregnant women; prenatal